Evaluating the Impact of â€œWork From Home Policyâ€ on Job Performance (Study Case in Indonesia) - Hutajulu, Richard Surungan (Universitas Negeri Semarang, 2021)
To determine the effect of work-from-home on job performance. It proposes work environment, job satisfaction and work motivation as mediating variables, and answers how work-from-home affects employee performance through them in Indonesia. A total of 713 valid respondents who answered the questionnaire came from employees in Indonesia, which were obtained from online social media. The data were tested for validity and reliability with SPSS 25.0 software, then the model was analyzed using Structural Equation Model (SEM) using AMOS 23.0 software. Based on statistical data processing it is known that working from home employees experience greater work motivation so that it can improve job performance, but it has no relationship with job satisfaction and work environment. The study has implications for business practitioner who intend to measure the effectiveness of their work-from-home policies. This is especially pertinent during the Work from Home policy. The original contribution of this study lies within its questionnaire that has been attuned to changes caused by Work from Home policy. This paper offers an important contribution on how the perception of work from home implication to job performance in human resources management academic.